THE EFFECT OF NEWS SITE QUALITY, SERVICES, AND TRUST ON BUSINESS INSIGHT SUBSCRIPTION DECISIONS (CASE STUDY ONLINE PREMIUM NEWS SUBSCRIPTION ON KONTAN ECONOMIC AND BUSINESS MEDIA, KOMPAS GRAMEDIA GROUP) - Ignatius Andri Indradie; Farida Indriani (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The purpose of this research is to test the influences of website design, and e service quality on e trust to impact e purchase decision. Using these variables, the use of these variables is able to solve the problems arising within Business Insight customers. The statement of this problem is how to increase e purchasing decision. The sample size of this research is 100 Business Insight customers. Using the SEM AMOS (Structural Equation Modeling). The results show that website design, and e service quality on e trust to impact e purchase decision. The effect ofweb designon e trust are significant; the effect ofe service qualityon e trust are significant; the effect ofweb designon e purchase decisions are significant; the effect ofe service quality on e purchase decisions are significant; the effect ofe truston e purchase decision is significant.